Individualized prosthetic rehabilitation in an ocular defect of traumatic origin. Case report. - Laura-Cahuana, Jessica Gabriela (2020)
Ocular trauma is the most frequent cause of eye loss worldwide. It can occur at any stage of life, with a higher incidence in childhood. Management can be surgical, surgical - prosthetic or prosthetic. We describe individualized prosthetic rehabilitation in a clinical case of upper eyelid ptosis, collapse and muscle atrophy due to lack of function following evisceration in a traumatic unilateral ocular injury approximately 56 years previously. We describe the technique for making ocular shapers to correct ptosis of the upper eyelid and achieve gradual expansion of the cavity, as well as the preparation of an ocular prosthesis to fulfill the expected functional and esthetic requirements.